A novel energy harvest method based on the vortex-induced vibration of a circular cylinder in a confined channel for the self-powered buoy. (1st April 2023) - Zhang, Rui; Huang, Lianzhong; Wang, Kai; Ma, Ranqi; Li, Boyang; Zhang, Baoshou
Abstract: A novel method to supply power to the buoy including vortex-induced vibration (VIV) system is proposed. The VIV response and energy conversion performance of an elastically mounted circular cylinder placed in a confined channel under a buoy is investigated. Two-dimensional simulations are conducted and the correctness of the numerical model is verified by comparison with experimental data. Four different width channels, 2 D, 3 D, 4 D, and 5 D ( D is three times cylinder diameter) are considered at flow velocities changes from 0.2 m/s to 1.3 m/s (1.77 × 10 4 <Reynolds number<1.15 × 10 5 ), and are compared with that in Open space. Results show that the narrower channel case has greater amplitude and power before the VIV amplitude reaches a peak, which is friendly for applications of the self-powered buoy. Later, the amplitude and power rise monotonically as the imposed width increase up to 5 D . The peak amplitude of the 2 D case (amplitude ratio A * = 0.74) is reduced by 8.3% compared with that of the Open case ( A * = 0.81). Besides, the maximum energy conversion efficiency (37.4%) is obtained in the narrowest channel, even if the maximum power of 3.69 W belongs to the 5 D case. Finally, the critical channel width of 5 D means the influence of the channel effect can be neglected. Highlights: A novel method to supply power to the buoy including VIV system is proposed. Confined channel has both negative and positive influence on VIV response. The amplitude is gradually suppressed as the width decreases in lower branch. The maximum energy conversion efficiency is achieved at narrowest channel. The channel effect can be ignored when the width > 15-cylinder diameter.